2009
DOI: 10.1080/09500830903236020
|View full text |Cite
|
Sign up to set email alerts
|

Favorable microstructural modulation and enhancement of mechanical properties of Ti–Fe–Nb ultrafine composites

Abstract: Microstructure evolution and its influence on the mechanical properties of (Ti 65.5 Fe 34.5 ) 100Àx Nb x (x ¼ 0, 3, 5 and 7) ultrafine composites has been investigated. The Nb-containing alloys exhibit simultaneously improved compressive mechanical properties, i.e. high yield (1.9-2.2 GPa) and fracture (2.2-2.6 GPa) strength together with large plasticity (6-13%), due to a favorable modulation of their ultrafine eutectic microstructure. The enhanced mechanical properties are strongly related to the lengthscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The (Ti 65 Fe 35 ) 89.15 Sn 3.85 Nb 7 alloy exhibits a significantly decreased strength as shown in figure . The (Ti 65 Fe 35 ) 93.15 Sn 3.85 Nb 3 alloy reveals a similar plastic strain and a higher compressive strength in comparison with the (Ti 65 Fe 35 ) 93 Nb 7 (2.57 GPa) and alloy . Figure displays SEM secondary electron (SE) images of the fracture surfaces of the specimens after compression at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The (Ti 65 Fe 35 ) 89.15 Sn 3.85 Nb 7 alloy exhibits a significantly decreased strength as shown in figure . The (Ti 65 Fe 35 ) 93.15 Sn 3.85 Nb 3 alloy reveals a similar plastic strain and a higher compressive strength in comparison with the (Ti 65 Fe 35 ) 93 Nb 7 (2.57 GPa) and alloy . Figure displays SEM secondary electron (SE) images of the fracture surfaces of the specimens after compression at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“… reported that eutectic and hypereutectic Ti‐Fe alloys consisting of A2 β‐Ti and B2 TiFe phases show a strength of ∼2 GPa and reasonable ductility of 4–7% in compression. The improved mechanical properties of eutectic and hypereutectic Ti‐Fe alloys have been reported by the additions of third elements such as Sn, Ga, Co, Ta, and Nb . The addition of 3.85 at.% Sn to eutectic Ti‐Fe alloys results in the increased strength and ductility .…”
Section: Introductionmentioning
confidence: 96%
“…Recently, less-costly, lower-density binary Ti-Fe alloys with ultrafine β-Ti plus TiFe microstructures were observed to exhibit a strength of 2000 MPa and 4-7% ductility [5,6]. Additions of Sn, Ta, Co, and Nb can further increase the strength and ductility of eutectic and hypereutectic Ti-Fe alloys [5][6][7][8][9][10][11]. Zirconium and titanium are congener transition metal elements in Group IV of the periodic table.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, ductile bimodal ultrafine eutectic composites without additional micrometer-size toughening phase have been developed [12][13][14][15]. In this case, the length scale heterogeneity of the eutectic phase contributes to the plasticity enhancement in such high strength nano-/ultrafine eutectic composites [16][17][18][19].…”
Section: Introductionmentioning
confidence: 97%